'Drugs for children' - an excellent new guide. Issue 18 (5th September 1988) - Unknown
Abstract : This book "aims to outline the principles and problems of drug use in children and to help physicians increase their appreciation and knowledge of specific problem areas". It is a short (180 page) handbook on safe and effective therapy for all who prescribe for children outside hospitals; it is not a textbook of paediatic pharmacology or therapeutics. The book has been produced by the WHO Regional Office for Europe. The editor and the main contributors are paediatricians from Britain, but many experts from 14 other countries helped to prepare the text, so that it is not insular.